Kerala's Plachimada Struggle A Narrative on Water and Governance Rights - C R BIJOY (Economic and Political Weekly October 14, 2006, 2006)
The struggle in Plachimada, Kerala, against Coca-Cola not only raises issues of mindless destruction of groundwater by a multinational company, but also exposes the gross inadequacies in the laws of governance and the rights to water. It also exposes the inability of political democracy, as we know it, to address weaknesses in law and governance. The state government meekly surrendered the opportunity that the struggle bestowed at the altar of the judiciary, rather than take advantage of it for bold political decision-making. The Plachimada struggle calls for the recovery of the commons by communities.